Implementasi Program UKGS (Usaha Kesehatan Gigi Sekolah) dan Dampaknya Terhadap Kebersihan Gigi Dan Mulut Di SD Inpres Unggulan BTN Pemda Makassar - Abdullah, Nurwiyana; Asridiana; A.Nurfaizah Pramudya; Johnny Angki (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2024)
Dental and oral health problems, especially hygiene problems (OHI-S), are still often found in school children and adults. Dental and oral hygiene is a condition that shows that a person's oral cavity is clean from plaque, debris and calculus. This disorder triggers bacterial invasion to stick to the teeth and gums. School Dental Health Business (UKGS) is an effort to implement dental health in elementary school children by paying attention to the three main points of the UKGS program, namely providing dental and oral health education, health services and environmental development, so that optimal levels of dental and oral health can be achieved for school children. The UKGS program has been implemented for a long time, but dental health in school-age children is still not optimal, the aim of implementing UKGS is to improve dental and oral hygiene in school children. The method used is a quantitative method, with a cross sectional design with a sample of 85 people. Data from the results of the OHI-S examination and the results of interviews will be analyzed using SPSS 23. The implementation of UKGS at the BTN Pemda Inpres Primary School, in this research shows that there is no relationship between UKGS and dental and oral hygiene in students, although there are still several other factors which supports the dental and oral hygiene of students at SD Inpres Unggulan BTN, Makassar Regional Government.